The role of hope, academic thriving, and adaptive coping in fostering peace of mind among university students: a mixed-methods study - Jing Shan; Jing Shan; Teng Xu (Frontiers in Psychology)
IntroductionUniversity students face significant academic stress, making psychological resources like hope, academic thriving, and adaptive coping essential for emotional well-being. Drawing on Snyder's Hope Theory and Schreiner's model of academic thriving, this study examines how these psychological constructs contribute to students' peace of mind.MethodsThis mixed-methods study collected quantitative data from 562 undergraduate students in mainland China using validated measures of hope, academic thriving, adaptive coping, and peace of mind. Structural equation modeling (SEM) was used to analyze the quantitative data. Qualitative data were gathered through semi-structured interviews and reflective journals to provide additional context.ResultsThe quantitative analysis revealed that hope and academic thriving are both directly and indirectly associated with peace of mind, with adaptive coping playing a significant mediating role. Specifically, higher levels of hope and thriving predicted greater use of adaptive coping strategies, which, in turn, enhanced students' emotional tranquility and mental clarity. The qualitative data provided nuanced insights into how students' hope, thriving, and coping strategies shaped their experiences of peace of mind.DiscussionThe findings suggest that promoting hope, fostering academic thriving, and teaching adaptive coping techniques can help students navigate academic challenges while maintaining emotional balance. These results have practical implications for educational interventions, highlighting the value of integrating psychological support into university settings to enhance both academic success and emotional well-being.